Toward a resonant society : An interview with Hartmut Rosa (Sociologisk Forskning, 2023)
In this interview, the internationally renowned German sociologist Hartmut Rosa engages in a conversation about resonance, critical theory, politics, and sociology. Rosa discusses populist politics and emotions, and he frames this discussion through his concept of resonance and its implications for politics and democracy. The interview was made in connection with a public lecture Rosa held in Gothenburg in March 2023, titled In search of the prime mover: Can there be a valid conception of social energy?
Keywords: resonance; critical theory; alienation; politics; climate change